Diet patterns and the incidence of age-related macular degeneration in the Atherosclerosis Risk in Communities (ARIC) study. Issue 8 (6th December 2019) - Dighe, Shruti; Zhao, Jiwei; Steffen, Lyn; Mares, J A; Meuer, Stacy M; Klein, Barbara E K; Klein, Ronald; Millen, Amy E
Abstract : Background: Age-related macular degeneration (AMD) is the leading cause of irreversible vision loss among the elderly. Objective: This study aimed to determine the association between dietary patterns and food groups (used to make them) with the 18-year incidence of AMD. Methods: ARIC (Atherosclerosis Risk in Communities) participants who showed change in AMD lesions between retinal photographs taken at visit 3 and visit 5 were graded side by side to determine incident AMD (any=144; early=117; late=27). A 66-line item food frequency questionnaire, administered at visit 1 and visit 3, was used to identify 29 food groups. Principal component analysis was used to derive dietary patterns from average food group servings. Logistic regression was used to estimate ORs and 95% CIs for incident AMD (any, early and late) by tertiles of dietary pattern scores, adjusted for age, race, education, total calories and smoking status. P-trend was estimated using continuous scores. Results: Western (unhealthy) and Prudent (healthy) dietary patterns were identified. No significant associations were observed between either dietary pattern and incident any or incident early AMD. However, a threefold higher incidence of late AMD was observed among participants with a Western pattern score above, as compared with below, the median (OR=3.44 (95% CI 1.33 to 8.87), p-trend=0.014). The risk of developing late AMD was decreased, but not statistically significant, among participants with a Prudent pattern score above, as compared with below, the median (OR=0.51 (95% CI 0.22 to 1.18), p-trend=0.054). Conclusions: Diet patterns were not significantly associated with incident any or incident early AMD. However, consumption of a Western pattern diet may be a risk factor for development of late AMD.